(untitled) (Teacher Education through Flexible Learning in Africa (TETFLE), 2021)
Learning activities constitute a very important component of distance education materials. They are associated with active learning and learning by doing, which are widely accepted as effective learning approaches. Learning by doing is particularly significant in distance education because distance learners have to teach themselves or learn on their own through doing and reflecting. This article reports and reflects on research which focused on the distance education materials designed by the University of Rwanda’s College of Education to provide professional development opportunities for high school teachers of English in Rwanda. Findings from a textual analysis of the materials and from interviews with a sample of teachers who had used these materials indicate that most of the activities were designed solely for ‘assessment of learning’ purposes and encourage a surface approach to learning. It is argued that activities which encourage a surface approach to learning limit learners’ engagement with, and understanding of, the content in the materials and improvement in quality teaching, a key goal of teacher professional development.